2020
DOI: 10.1590/01047760202026022723
|View full text |Cite
|
Sign up to set email alerts
|

Study of Thermal Expansion and Compression Strength of Three Wood Species From Plantations

Abstract: Dimensional changes during thermal treatment were evaluated by dilatometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Combined with the results of wet chemical analysis and FT-IR, it could be determined that the decrease of In general, the linear expansion coefficient along the grain direction (α l ) of sound wood is close to zero, only about 10% of that in the transverse grain direction. The radial linear expansion coefficient is smaller than that in the tangential direction [46][47][48]. The tendency of linear expansion of the three groups of archaeological wood samples in three directions was different from that of the sound wood.…”
Section: Discussionmentioning
confidence: 99%
“…Combined with the results of wet chemical analysis and FT-IR, it could be determined that the decrease of In general, the linear expansion coefficient along the grain direction (α l ) of sound wood is close to zero, only about 10% of that in the transverse grain direction. The radial linear expansion coefficient is smaller than that in the tangential direction [46][47][48]. The tendency of linear expansion of the three groups of archaeological wood samples in three directions was different from that of the sound wood.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown a negative correl tion between the modulus of rupture (MOR) and modulus of elasticity (MOE) of woo which can be used to predict bending performance [25][26][27]. Different positions even o the same log can also have very different physical properties [28][29][30]. To date, there are n research reports on the effects of growth ring width and tree height on the transver compression performance of wood.…”
Section: Methodsmentioning
confidence: 99%
“…The hygroscopic shrinkage/expansion is caused by evaporation/absorption of water from/by the bark to/from the surrounding air during low/high atmospheric relative humidity Ilek et al, 2017;Delapierre et al, 2023). The stem shrinkage and expansion caused by variation in temperature is minimal, and the thermal expansion is lower in dry wood than in fresh/wet wood (Sevanto et al, 2005;Zhao et al, 2016;Goli et al, 2019) and lower in the radial direction than in the tangential direction (Espinoza-Herrera et al, 2020).…”
Section: Introductionmentioning
confidence: 99%